Prevalence, Milk Yield, Composition, and Treatment of Subclinical Mastitis in Crossbred Cows: Exploring Economic of Mastitis and Alternative Approaches beyond Conventional Antibiotics- A Field Study - Kachhawaha, Subhash; Bhagwat Singh Rathore (Annals of Arid Zone, 2025)
Bovine sub-clinical mastitis (SCM) is a major constraint to the dairy industry throughout the word. SCM presents no clinical symptoms and unnoticed by the dairy owner. Early detection and treatment of SCM is of paramount importance to check spread of the disease into clinical form of mastitis. A study was undertaken to assess the effectiveness of herbal gel application in sub-clinical mastitis (SCM) and effect on milk quality. The study was carried out during the period from January 2020 to December 2024 in five small dairy units in the Jodhpur district of Rajasthan. Fifty lactating cross bred cows were selected in third to fifth lactation with milk yield ranging 15-20 L day-1 from adopted villages of Krishi Vigyan Kendra, Jodhpur. Sub-Clinical Mastitis was diagnosed on the basis of Mastitis Detection Strip (MDS) on milk. Overall prevalence was reported 22.85%. As the condition progressed, milk yield declined significantly until treatment was administered. Average milk production increased by 12.1% after the treatment. In this study, a non-antibiotic topical herbal gel demonstrated a high efficacy of 84% in controlling subclinical mastitis in lactating cows. It is hypothesized that the herbal ingredients not only enhance natural immunity at the cellular level but also strengthen udder integrity and defence mechanisms. This may occur through the combined effects of cellular activation within the mammary glands, improved bacterial clearance by phagocytic cells, and regulation of acute inflammatory responses. Consequently, this investigation aimed to evaluate the field efficacy of the herbal topical gel as a non-antibiotic treatment for subclinical mastitis, facilitating its transfer as a practical management strategy.